Moral conscience: widening its application in health. Theoretical and practical issues of moral judgment in Chile - Valderrama Sandoval, Antonieta; López Barreda, Rodrigo (Acta Bioethica, 2011)
Generally, conscience is understood as an individual and subjective character of human being; nevertheless, re- cently its rational character has been highlighted and subjected to external evaluation criteria. The application of moral conscience judgments is transversal to all health care fields, even in daily relations with patients. Health care professionals conscience objection has been criticized because it could neglect professional responsibility; never- theless, to follow an honest conscience is a moral duty for all, independently of role fulfilled in a certain moment. To prevent to do it means to damage autonomy and moral integrity of who seeks to act in conscience.